Biodegradation competence of Streptomyces toxytricini D2 isolated from leaves surface of the hybrid cotton crop against β cypermethrin. (August 2021) - Whangchai, Kanda; Van Hung, Tran; Al-Rashed, Sarah; Narayanan, Mathiyazhagan; Kandasamy, Sabariswaran; Pugazhendhi, Arivalagan
Abstract: The frequent application of β cypermethrin in farming activity, causing severe soil and water contamination. Thus, finding a suitable microbial agent to degrade the toxic pesticide into less or nontoxic components is vital. Hence, β cypermethrin-resistant predominant bacteria from the pesticide-exposed surface of cotton leaves were isolated and optimized the growth conditions required for the significant degradation of β cypermethrin. Six dominant bacterial cultures were isolated from pesticide exposed cotton leaf samples, and among them, COL3 showed better tolerance to 6% of β cypermethrin than others. This COL3 was identified as Streptomyces toxytricini D2 through the 16S rRNA analysis. The suitable growth requirements of S. toxytricini D2 were optimized with various essential growth parameters to degrade β cypermethrin and the results showed that a significant degradation of β cypermethrin was observed at 35 °C, pH 8.0, 1.5% of inoculum, and nutritional factors like glycerol (20 mg L −1 ), ammonium sulfate (15 mg L −1 ), and calcium phosphates (10 mg L −1 ) were served as better carbon, nitrogen, and phosphate sources respectively. The degradation percentage and half-life of β cypermethrin were calculated as 80.71 ± 1.17% and 48.15 h respectively by S. toxytricini D2. The GC-MS analysis results showed that S. toxytricini D2 effectively degraded the β cypermethrin into 5 components such as methyl salicylate, phenol, phthalic acid, 3-phenoxy benzaldehyde, and 3-PBA. This is the first report, revealed that the S. toxytricini D2 belongs to the Actinobacteria has the potential to degrade the β cypermethrin into less or nontoxic metabolites under optimized conditions. Highlights: Pesticide degrading S. toxytricini D2 isolated from surface of pesticide exposed cotton leaves. This is the first report on S. toxytricini D2 ( Actinobacteria ), has pesticide degrading potential. Suitable growth conditions of S. toxytricini D2 were optimized for degradation of β cypermethrin. Under optimal conditions S. toxytricini D2 degrading 80.71% of β cypermethrin (within 12 days). S. toxytricini D2 has potential to degrading toxic metabolite 3-PBA into nontoxic components.